A Chimera Oscillatory State in a Globally Delay-Coupled Oscillator Network. (7th May 2020) - Yi, Ming; Yao, Chenggui
Abstract : Oscillatory behavior is absolutely necessary for the normal functioning of various organisms and their performance. Therefore, it is necessary to protect the oscillatory behavior in an aging network which consists of oscillatory and nonoscillatory nodes. In this work, we investigate numerically and theoretically the effect of time delay on oscillatory behaviors in a network which includes active and inactive Stuart–Landau oscillators. Interestingly, we find a chimera oscillatory state where a part of oscillators is a steady state while other oscillators preserve oscillatory motion; such dynamical behaviors are considered generally to be impossible for globally coupled systems when the coupling strength is sufficiently large. Furthermore, our results reveal that time delay can effectively inhibit aging transition and recover the oscillatory behavior from the aging network.